2006
DOI: 10.1128/jb.188.5.1710-1720.2006
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Control of aparABPromoter Leads to Formation of Sporulation-Associated ParB Complexes inStreptomyces coelicolor

Abstract: Here we have analyzed the transcriptional regulation that underpins this developmentally specific behavior. Analysis of promoter mutations showed that the irregularly spaced complexes present in vegetative hyphae are dependent on the constitutive parABp 1 promoter, while sporulationspecific induction of the promoter parABp 2 is required for the assembly of arrays of ParB complexes in aerial hyphae and thus is necessary for efficient chromosome segregation. Expression from parABp 2 depended absolutely on two sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 50 publications
4
54
0
Order By: Relevance
“…The formation of ParB complexes in the aerial hyphae of S. coelicolor is dependent on the developmental induction of the parAB promoter. Thus, ParB complexes were not observed in the nonsporulating (white) Streptomyces mutants (70). Earlier studies showed that in S. coelicolor, as in other bacteria, the ParA protein is required for efficient formation and regularly spaced placement of ParB complexes (42).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of ParB complexes in the aerial hyphae of S. coelicolor is dependent on the developmental induction of the parAB promoter. Thus, ParB complexes were not observed in the nonsporulating (white) Streptomyces mutants (70). Earlier studies showed that in S. coelicolor, as in other bacteria, the ParA protein is required for efficient formation and regularly spaced placement of ParB complexes (42).…”
Section: Discussionmentioning
confidence: 99%
“…SMC complexes are transiently localized at the time of sporulation, when DNA has to be compacted and segregated. Thus, SMC, like FtsZ (8) and ParAB (19,20), seems to belong to the larger group of proteins whose expression is highly induced in response to the requirement of aerial hyphal maturation. The SMC foci, like FtsZ and ParAB, disappear after septation.…”
Section: Discussionmentioning
confidence: 99%
“…S. coelicolor WhiA binds to its own promoter and is required for its own expression (26,50), the sporulation-dependent expression of ftsZ, and the expression of other sporulation genes (27,51,52). The nucleoidbinding activity of YvcL and its homology to WhiA suggest that YvcL functions as a transcription factor, possibly regulating ftsZ expression.…”
Section: Synthetic Lethal Screenmentioning
confidence: 99%